A SEER database retrospective cohort of 547 patients with penile non-squamous cell carcinoma: demographics, clinical characteristics, and outcomes - Ashley, Lucas W.; Sutton, Kent F.; Ju, Andrew; Edwards, George; Pasli, Melisa; Bhatt, Arjun (Frontiers in Oncology, 2023)
Introduction: Little research has investigated the prevalence and distribution of the diverse pathologies of non-squamous cell carcinoma (non-SCC) of the penis. Although rare in clinical practice, these cancers have become a focus of greater importance among patients, clinicians, and researchers, particularly in developing countries. The principal objective of this study was to analyze the major types of penile non-squamous cell carcinoma, elucidate common treatment pathways, and highlight outcomes including 5-year survival. Materials/methods: The Surveillance, Epidemiology and End Results (SEER) database was queried between 2000 to 2018 to identify a retrospective cohort of patients with penile non-SCC. Demographic information, cancer characteristics, diagnostic methods, treatments administered, and survival were investigated. Results: 547 cases of penile non-SCC were included in the analysis. The most prevalent non-SCC cancers included epithelial neoplasms, not otherwise specified (15.4%), unspecified neoplasms (15.2%), basal cell neoplasms (13.9%), blood vessel tumors (13.0%), nevi and melanomas (11.7%), and ductal and lobular neoplasms (9.9%). Over half (56.7%) of patients elected to undergo surgical intervention. Patients rarely received systemic therapy (3.8%) or radiation (4.0%). Five-year survival was 35.5%. Patients who underwent surgery had greater annual survival for 0 to 10 years compared to those who did not have surgery. Significant differences in survival were found between patients who had regional, localized, and distant metastases (p<0.05). A significant difference in survival was found for patients married at diagnosis versus those who were unmarried at diagnosis (p<0.05). Lower survival rates were observed for patients older than 70 years. Discussion: Although less prevalent than squamous cell carcinoma, penile non-SCC encompasses a diverse set of neoplasms. Patients in this cohort had a high utilization of surgical management leading to superior outcomes compared to those not receiving surgery. Radiation is an uncommonly pursued treatment pathway. Patient demographics and socioeconomic variables such as marital status may be valuable when investigating cancer outcomes. This updated database analysis can help inform diagnosis, management, and clinical outcomes for this rare group of malignancies.